Supervisi Akademik Dalam Meningkatkan Kompetensi Guru di Lembaga Pendidikan Islam - Rohmat Rohmat (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2015)
AbstractSupervision focuses on the academic supervisor observation of the academic activity, in the form of learning both inside and outside the classroom. Managerial supervision focuses on observations on aspects of management and administration of the school that serves as a support (supporting) the implementation of learning. Supervisors are mediators educational duties as a supervisor at educational institutions have to perform tasks and functions. The key task of the supervisor are basically three; supervise, assess and develop. And in order to improve the competence of teachers, through the implementation of academic supervision, should adopt the model of empowerment paradigm desire, trust, confident, credibility, accountability and communication. AbstrakSupervisi akademis menitikberatkan pada pengamatan supervisor terhadap kegiatan akademis, berupa pembelajaran baik di dalam maupun di luar kelas. Supervisi manajerial menitikberatkan pada pengamatan pada aspek-aspek pengelolaan dan administrasi sekolah yang berfungsi sebagai pendukung (supporting) terlaksananya pembelajaran. Pengawas adalah mediator pendidikan yang menjalankan tugas sebagai supervisor di lembaga pendidikan yang harus menjalankan tugas dan fungsinya. Tugas pokok pengawas pada dasarnya ada tiga; mengawasi, menilai, dan membina. Dan dalam rangka meningkatkan kompetensi guru, melalui implementasi supervisi akademik, hendaknya mengadopsi model pemberdayaan dengan paradigma desire, trust, confident, credibility, accountability dan communication.